Effect of Cilostazol on the Pharmacokinetics of Simvastatin in Healthy Subjects. (9th January 2019) - Kim, Jung-Ryul; Jung, Jin Ah; Kim, Seokuee; Huh, Wooseong; Ghim, Jong-Lyul; Shin, Jae-Gook; Ko, Jae-Wook
Abstract : Purpose . We evaluated potential drug-drug interactions between cilostazol and simvastatin, both CYP3A substrates, in healthy subjects. Methods . An open-label, two-period, fixed-sequence clinical study was conducted. Seventeen subjects were given a single oral dose of simvastatin 40 mg on day 1 and multiple oral doses of cilostazol 100 mg twice daily on days 2 to 5 followed by a single dose of cilostazol and simvastatin on day 6. Plasma concentrations of simvastatin and its active metabolite, simvastatin acid, were measured using liquid chromatography-tandem mass spectrometry for pharmacokinetic assessment. Moreover, serum lipid profiles under fasting conditions were determined. Results . The geometric mean ratios of the area under the plasma concentration-time curve from time zero to time infinity of simvastatin combined with cilostazol to that of simvastatin alone were 1.64 (90% CI, 1.38-1.95) for simvastatin and 1.31 (1.04-1.66) for simvastatin acid. In addition, coadministration with cilostazol significantly increased the maximum concentration of simvastatin and simvastatin acid, up to 1.8-fold and 1.6-fold, respectively. However, the effects of a single dose of simvastatin on serum lipid profiles were not affected notably when simvastatin was coadministered with cilostazol. Conclusions . Multiple doses of cilostazol increased the systemic exposure of simvastatin and simvastatin acid following a single dose of simvastatin.